Pengaruh Promosi Kreatif dan Variasi Produk terhadap Keputusan Pembelian pada Konsumen E-commerce Zalora.co.id (Studi Kasus pada Konsumen di Kota Jakarta) - Disa Fitri Pradwika; Sudharto Prawata Hadi (Universitas Diponegoro, 2019)
Business development in the online fashion sector or e-commerce is now developing along with the rapid development of technology. As an online clothing ecommerce initiator, Zalora.co.id has lost competition with the new emerging e-commerce, one of which is a decreasing number of purchases. Purchasing decisions are the goals that must be achieved by every business company. To achieve this goal, Zalora.co.id needs to pay attention to what things that can affect purchasing decisions. This study aims to determine the effect of creative promotion and product variety on Zalora.co.id e-commerce consumers purchasing decisions. The type of research used is explanatory research. Samples taken are 100 respondents who had made purchases on the Zalora.co.id website. The sampling technique used is accidental sampling. Data collection techniques used are questionnaires, observations, and literature studies. Data analysis methods used are validity test, reliability test, correlation test, simple linear regression test, multiple linear regression test, determination coefficient (R2), and significance t test and f test with the help of IBM SPSS program version 22.0. Based on the results of the analysis, it can be concluded that creative promotion and product variety have an effect on purchasing decisions proven through the simple regression test with the result in regression values of 0,432 and 0,791. The advice given to the company is to improve the promotion that has been carried on to make it more unique and different from other e-commerce promotions and re-evaluate the product variation strategy.